Hul’q’umi’num’ stories as snuw’uyulh: Bringing life lessons to language learners - Antoine, Laura (2019)
The Hul’q’umi’num’ are a Coast Salish people who live on Vancouver Island. This project attempts to inspire my fellow First Nations people to learn the Hul’q’umi’num’ language by learning the sacred cultural teachings (snuw’uyulh) passed from generation to generation. It focuses on teachings from my mother and my grandmothers. My mother taught me that everything is connected and interconnected, everything we do has purpose, and culture and language go hand-in-hand. As is our cultural practice, the teachings are embedded in a set of stories drawn from my personal experiences. The research is framed in the context of language revitalization. My hope is that non-Hul’q’umi’num’ speakers who want to understand the teachings will be inspired to also learn the language.